Development of Automatic tekong Launcher System - Muhammad Adib, Shaharun; Mohd Tarmizy, Che Kar; Mohd Sazali, Salleh; Mohd Idzwanrosli, Mohd Ramly; Wan Hassan, Wan Hamat (UMPSA, 2024)
The historical evidence indicates that sepak takraw was played in the 15th century in Malaysia, and today, it stands as one of the most popular sports in the country. Despite being the birthplace of sepak takraw and a regular participant in prestigious events like the Commonwealth Games, Asian Games, and Southeast Asian Games, Malaysia faced a setback when the National Sports Council (MSN) removed sepak takraw from its list of national core sports in 2017 due to poor performance.